2010
DOI: 10.5551/jat.2832
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension Among Middle-Aged and Elderly People in Taiwan: A Five-Year Follow-Up

Abstract: Aim:To evaluate the prevalence of prehypertension among middle-aged and elderly people in Tai Conclusions:The prevalence of prehypertension among older Taiwanese was 35.8% and the 5-year cumulative incidence of hypertension from prehypertension was 31.3%. Older prehypertensive subjects with higher pulse pressure, higher serum total cholesterol and higher low-density lipoproteincholesterol were more likely to become hypertensive within 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
6
3
Order By: Relevance
“…On the contrary, the prehypertension estimate in our sample was lower when compared with the results reported from Taiwan (35.8%), U.S.A. (36.3%) and China (38.4% and 44.1%) [6,7,13,17-23]. However, the present findings contradict the Jamaica Study’s gender specific pattern whereby men (35.0%) rather than women (25.0%) exhibited higher percentages of pre-hypertension [6].…”
Section: Discussioncontrasting
confidence: 97%
“…On the contrary, the prehypertension estimate in our sample was lower when compared with the results reported from Taiwan (35.8%), U.S.A. (36.3%) and China (38.4% and 44.1%) [6,7,13,17-23]. However, the present findings contradict the Jamaica Study’s gender specific pattern whereby men (35.0%) rather than women (25.0%) exhibited higher percentages of pre-hypertension [6].…”
Section: Discussioncontrasting
confidence: 97%
“…Prehypertension affected about one third (35.7%) of suburban adults in Beijing, and the prevalence was higher in men than in women in all age categories, which is generally consistent with other published studies (30% in Jamaica, 16 31% in the United States, 17 31.6% in Korea, 18 32% in Japan, 19 35.8% in Taiwan, 20 and 40% in the Ashanti region of Ghana). 21 The results of these studies reveal that the prevalence of prehypertension is high in both developed and developing countries, and that prevalence in developing countries is rapidly approaching that in developed countries.…”
Section: Discussionsupporting
confidence: 91%
“…18 A recent study conducted in 5 Indian cities showed that the prevalence of prehypertension in Indian adults was only 28.7% (27.2% in women, and 30.0% in men). 19 Other published studies in developed countries of Asia reported that the prevalence of prehypertension was 31.6% in Korea, 20 32% in Japan, 21 and 35.8% in Taiwan, 22 which are all lower values than the prehypertension percentage in the present study. Even compared with results from Europe and America, the prevalence of prehypertension in urban Chinese adults in northeast China is still higher.…”
Section: Discussioncontrasting
confidence: 51%